Victim-centred peacemaking: Colombia's Santos-FARC-EP peace process - Brett, Roderick Leslie (Bristol University Press, 2025)
Based on unique empirical research into Colombia's Santos-FARC-EP peace process (2012-2016), this book interrogates how, if at all, survivors and victims may assert agency and contribute to formal peacemaking and transitional justice initiatives. The book argues that victim inclusion meaningfully transformed victim-perpetrator relations and dynamics in Havana, while partially shaping the content of both the Victims' Agreement and Final Agreement. As such, the delegations created paths for empowerment at the individual and, in part, collective levels. However, victim inclusion also precipitated experiences of victim depoliticization, revictimization, retraumatization and instrumentalization.